Official data on investments in environmental protection: Data documentation (2005-2016) - Julia Rechlitz (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
[Introduction] The Research Data Centers of the Statistical Offices of the Federation and the Federal States (RDCs) make a large variety of micro-level data sets on German firms, the Amtliche Firmendaten in Deutschland (AFiD) available. The official data on investments in environmental protection (IEP data) is one of those AFiD modules and records the annual investments in environmental and climate protection in Germany.1 It is a primary survey conducted by the Statistical Offices of the Federal States and aims to provide a profound data basis for future environmental policy decisions (RDCs 2020a). The data set is an official statistic to which most firms and plants in the manufacturing sector are legally obliged to report their sustainable investments. It surveys the different types of environmental investments and reports the investment volume annually. The data is subject to several plausibility checks, which ensure high data quality (RDCs 2020a). This comprehensive data set is a valuable data source since it provides a broad picture of the investment in environmental and climate protection in Germany. It allows the user to track the development of different types of sustainable investments over time and reports information on the investing firm. The IEP data is a complete survey with cut-off limits which only exclude small firms. Hence, empirical studies based on the IEP data can benefit from a high external validity. This data documentation describes the content of the official data on investments in environmental protection. As the data set is not publicly available, it is important to give some insights into the IEP data to researchers and other data users without access. Besides providing a definition of all variables contained and some further descriptive analysis, the documentation draws attention to particularities in the structure of the data set and some variables. It joins a series of other data documentations on other AFiD modules.2 Also, the complete source codes on which the IEP data documentation is based are freely accessible for future data users as open-source code.3 The data documentation is structured as follows: After this introduction, Section 2 explains the structure of the IEP data set in greater detail. It explains the difference between the firm- and plant-level in the data set, provides information on their main economic activity, and describes sample sizes. Section 3 explains the different data access options. Section 4 reports the content of the IEP data in detail. In separate subsections, each group of variables is introduced, the number of cases per variable is presented, and some descriptive analyses are shown. Section 5 closes with an overview of different merge possibilities with other AFiD modules.
Keywords: 330